Mineralogia, tipologia e causas de cor de espodumênios da Província Pegmatítica Oriental do Brasil e química mineral de NB-tantalatos da mina da Cachoeira (Minas Gerais) - Coralie Heinis Dias (2015)
Spodumene (LiAlSi2O6) is a lithium-bearing mineral, which occurs mainly in pegmatites. Besides its use as an important lithium source, it is also a gemmologic mineral, with its varieties: pink (kunzite), emerald-green (hiddenite) and green/yellowish-green. However, there has been few efforts in order to expand knowledge about its known occurrences and/or deposits in Minas Gerais State. In Brazil, spodumene occurs especially in heterogeneous pegmatites, within several deposits in the Eastern Brazilian Pegmatite Province (EBPP). EBPP encompasses a surface of about 150.000 km², and most of it is situated on the eastern part of Minas Gerais State, specifically in the geotectonic unit called Araçuaí Orogen. The aim of the present work was to study various pegmatite bodies in which different types and varieties of spodumene occur, in order to define its chemical aspects and causes of color, besides comparing such occurrences in the EBPP. The studied deposits were: Chapadinha (Itinga county), Cachoeira (Araçuaí/Itinga counties), Neves (Araçuaí county), Jairo Linguiça (Resplendor county), Sapucaia (Galiléia county), Urucum (Galiléia county) e Santa Rosa (Itambacuri county). In such deposits, samples of spodumene and feldspars were collected, in addition to Nb-tantalates from the Cachoeira Mine, analyzed by electron microprobe and/or ICP-MS. The latter minerals were also analyzed by X-ray diffraction, which allowed the recognition of ixiolite, a mineral that had never been described in the EBPP before. Besides, green/yellowish-green spodumene samples were submitted to electronic paramagnetic resonance (EPR) and optical absorption spectroscopy, in order to study its causes of color. Electron microprobe analysis revealed few variations which could be compared. However, it could be observed that green/yellowish-green spodumene samples showed iron contents significantly higher than pink spodumene samples. It could be established, through EPR and optical absorption analyses, that the yellow component of spodumene colors is caused by Fe3+ ion. In relation to the pegmatite environment in which spodumene occurs, most of the studied bodies is emplaced in schists, somewhat distant from the parent granite. Most of them are classified as wide (between 15 and 50 m) and all show significant fractionation degree, with regard to their fluids of formation. Finally, with regard to the variety of different spodumene types, it was observed that each one corresponds to distinct crystallization stages and, consequently, different environment/conditions of formation. Five different types of spodumene were distinguished, related to different formation stages of the pegmatite under primary to hidrotermal conditions, according to decreasing temperatures of crystallization.